Magnetic and Electronic Properties of Sr Doped Infinite-Layer NdNiO2 Supercell: A Screened Hybrid Density Functional Study - Yawen Hua; Meidie Wu; Qin Qin; Siqi Jiang; Linlin Chen; Yiliang Liu (Molecules, 2023)
To understand the influence of doping Sr atoms on the structural, magnetic, and electronic properties of the infinite-layer NdSrNiO2, we carried out the screened hybrid density functional study on the Nd9-nSrnNi9O18 (n = 0–2) unit cells. Geometries, substitution energies, magnetic moments, spin densities, atom- and lm-projected partial density of states (PDOS), spin-polarized band structures, and the average Bader charges were studied. It showed that the total magnetic moments of the Nd9Ni9O18 and Nd8SrNi9O18 unit cells are 37.4 and 24.9 emu g−1, respectively. They are decreased to 12.6 and 4.2 emu g−1 for the Nd7Sr2Ni9O18-Dia and Nd7Sr2Ni9O18-Par unit cells. The spin density distributions demonstrated that magnetic disordering of the Ni atoms results in the magnetism decrease. The spin-polarized band structures indicated that the symmetry of the spin-up and spin-down energy bands around the Fermi levels also influence the total magnetic moments. Atom- and lm-projected PDOS as well as the band structures revealed that <semantics>Ni(dx2−y2)</semantics> is the main orbital intersecting the Fermi level. As a whole, electrons of Sr atoms tend to locate locally and hybridize weakly with the O atoms. They primarily help to build the infinite-layer structures, and influence the electronic structure near the Fermi level indirectly.